GLOBAL TRENDS IN ARTIFICIAL INTELLIGENCE (AI) PRESCHOOL ISLAMIC EDUCATION MODULES: A BIBLIOMETRIC ANALYSIS - Salleh, Khadijah Aini; Abd Hamid, Samsuddin; Yusoff, Mohd Tarmizi; Salleh, Rashidah; Salleh, Zakiah; Kadir, Khairulzaman (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study investigates the global research landscape concerning Artificial Intelligence (AI) integration in preschool Islamic education modules, a niche yet growing intersection between digital technology and early childhood religious instruction. Despite increasing interest in AI across educational settings, limited bibliometric exploration has been conducted specifically within the context of Islamic preschool pedagogy. This gap presents a need to systematically scholarly trends, research outputs, and intellectual structures surrounding AI-supported Islamic education at the preschool level. This bibliometric analysis aims to identify publication patterns, key contributors, dominant themes, and collaborative networks that have shaped the field. Using a structured methodological approach, bibliographic data were extracted from the Scopus database. A total of 246 relevant documents published between 2000 and 2025 were retrieved and refined using OpenRefine for data cleaning. Subsequently, visualization and network mapping were conducted using VOSviewer software to explore co-authorship, keyword co-occurrence, and citation analyses. The results reveal an upward trajectory in publications post-2018, with notable contributions from countries such as Malaysia, Indonesia, Saudi Arabia, and the United Kingdom (UK). Keyword analysis highlights the prominence of terms such as “AI in education,” “Islamic pedagogy” and “early childhood learning”. However, limited cross-country collaboration and a lack of focused empirical studies on module development were observed. This study provides a foundational overview of scholarly progress in the field, offering insights for future research directions and policy formulation. It also contributes to the discourse on how AI technologies can be innovatively and ethically integrated into faith-based early childhood education, aligning digital advancement with spiritual and cognitive growth. Therefore, future work should explore empirical validation of AI-based modules and pedagogical models tailored to preschool Islamic contexts.